Prevalence of Serum Vitamin-B12 Level and its Association Among the Patients of Transient Ischemic Attack/Ischemic Stroke - Abdullah Khan, Shahida Hasan Memon, Rukhsana Saboor, Aneeb Mengal, Naila Memon, Muhammad Ali Soomro6, Kiran Aamir, Aamir Ramzan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the hospital-based prevalence of Vitamin-B12 deficiency in ischemic stroke patients and to compare the association of VitB-12 among patients of Ischemic stroke and controls. Study Design: Comparative study Place and Duration: Neurology and Medicine wards at the Liaquat University Hospital Hyderabad/Jamshoro. From Dec 2021 to June 2022 Methods: It was a non-probability convenience sample that comprised 263 individuals, of whom 132 were cases and 131 were controls. Among the participants, there were no missing data. The completion of a standardized questionnaire allowed for the collection of information about socio-demographic factors. Serum levels of VitB-12 were measured for all of the individuals aged 18 to 60 years old and of both genders Results: The gender distribution of cases and control groups, as well as the sociodemographic characteristics of the study population, have significant differences, in gender (p = 0.012) and socioeconomic status (p = 0.016). However, there was not a significant difference found in residence (0.82), nor age (0.46), in either of the groups. The average body mass index (BMI) was calculated to be 24.1 ± 6.1, while the average weight and height were determined to be 62.8 ± 12.3 kg and 158.62 ± 5.21cm, respectively. The incidence of ischemic stroke was recorded in 84 patients, whereas transient ischemic attack was documented in 48 patients. The percentage of instances that were affected by risk factors such as smoking, using paan gutka, or having high blood pressure was much greater than the percentage of cases that were affected by obesity, diabetic patients, or vegetarians. In all, there were 132 people out of 263 who were checked for their blood VitB-12 levels who were determined to have suffered from a stroke or transient ischemic attack (TIA). The cases comprised of both ischemic stroke or TIA. In a comparison of cases (ischemic stroke/TIA) and controls, it was shown that the patients had significantly lower mean levels of blood VitB-12 than the controls did (132.7+ 2.41 vs. 272.1+ 5.17 pg/mL respectively). Conclusion: The patients reported to neurology ward of Liaquat University hospital Hyderabad and Jamshoro, we found an unacceptably high burden of stroke and transient ischemic attack. There is a significant association between VitB-12 and ischemic stroke as compared to healthy controls. Keywords: Vitamin B-12, Ischemic Stroke, Risk Factors